(untitled) (Eurasian Medical Research Periodical, 2024)
The article is devoted to specific signs of nonspecific interstitial pneumonia detected by radial diagnostic methods. In particular, it is noted that patients are characterized by the predominance of "frosted glass" and absence of "honeycomb lung" in cellular subtype, and in fibrous or mixed subtype all four main radiologic syndromes, as well as (often, but not always) "honeycomb lung" are simultaneously expressed to different degrees. The presence of symmetrical thin subpleural thin strips of preserved lung tissue, followed by reticular and inflammatory changes is established.